Arabic Morphological Errors in the Writings of Traditional Pesantren Students in Yogyakarta: Integrating Error Analysis and Educational Ethnography: English - Muhammad Ivang Rizaldi; Daly Auliya Rahayu; Wati Susiawati; Mauidlotun Nisa (Universitas Djuanda, 2026)
The ability to write Arabic as the highest productive skill faces complex challenges for non-native learners, especially in the unique environment of traditional pesantren. This study aims to analyze the variations, causes, and cultural meanings of morphological errors in the writings of santri traditional Pesantren in Yogyakarta. Using an educational ethnographic approach, this study analyzes ten handwritten artifacts (imla’) accompanied by reflective interviews to integrate textual analysis and cultural interpretation. The results of the study identified seven categories of morphological errors, with hamzah writing errors (25.8%) being the most dominant, followed by idhafah errors and ha writing in fi'il. The analysis shows that these errors stem from complex interactions between interference from the mother tongue (Indonesian), intralingual learning strategies (such as overgeneralization and oversimplification), and the learning ecology of pesantren, which is centered on oral tradition and memorization. These findings imply the need for a pedagogical reorientation of Arabic morphology teaching in Islamic boarding schools that is more integrative and contextual, taking into account the santri's interlanguage and linking the rules to authentic literacy practices in the local scholarly tradition.